Mortality risk factors in kidney‐transplanted patients with COVID‐19: A systematic review and regression analysis. Issue 4 (4th November 2021) - Navari, Yasaman; Bagheri, Amir Behzad; Akhavan Rezayat, Arash; SeyedAlinaghi, SeyedAhmad; Najafi, Sara; Barzegary, Alireza; Asadollahi‐Amin, Ali
Abstract: Background and aims: The kidney transplant patients who receive immunosuppressive and specific medication may lead to different mortality risk factors between kidney transplant patients with COVID‐19 and the general population. We aimed to provide a model predictor and a risk analysis of mortality in kidney transplant COVID‐19 positive patients. Methods: We performed our search using PubMed, MEDLINE, Web of Science, Scopus, and Google Scholar to identify English articles published from the beginning of December 2019 through August 2020. Excluded manuscripts had no full text, lacked information, were not the original article, or consisted of less than three cases. We gathered information about demographic information, comorbidities, COVID‐19 symptoms, lung radiographic findings, history of medication therapy, and changes in the kidney maintenance therapy after confirming their COVID‐19 on the data extraction forms. Results: We found a total of 31 eligible articles. We set a 10% mortality rate as our cutoff point. The most common sign and symptoms were cough (53.22 [29.42]), dyspnea (50.80 [24.55]). In the bivariate analysis, fatigue ( P  = .04, OR of 0.92; 95% CI: 0.85‐1.00), hypertension ( P  = .07, OR of 1.03; 95% CI: 1.00‐1.07), and dyspnea ( P  = .08, OR of 1.04; 95% CI: 1.00‐1.09) showed a statistically significant relationship with increases in mortality. In multivariate regression analysis, an independent association was only found between hypertension and mortality ( P  = .035; AOR of 1.064; CL: 1.004‐1.127). Conclusion: Clinicians should pay special attention to modifiable risk factors for COVID‐19 infection mortality, such as hypertension among kidney transplant patients, because it may be possible to decrease mortality by controlling these factors.